A retrospective study of eyeball rupture in patients with or without orbital fracture. Issue 24 (June 2017) - Chen, Xiang; Yao, Yi; Wang, Fengxiang; Liu, Tiecheng; Zhao, Xiao
Abstract : Abstract: To summarize the clinical features of eyeball rupture with or without orbital fracture and explore the differences between them. In all, 197 patients were observed, and the following data were recorded: sex, age, time of injury, place of injury, cause of trauma, zone of eye injury, intraocular content prolapse, surgical methods and the therapeutic process, visual acuity after injury, and the final best corrected visual acuity. The results were analyzed for statistically significant differences. There was no significant difference ( P > .05) in the age, sex, or cause of injury. Patients with eyeball rupture with fracture had poorer vision than did those in the simple eyeball rupture group; eyeball rupture with fracture also had a higher probability of enucleation. In this study, the clinical results show that prognosis of eyeball rupture with orbital fracture is worse than that of eyeball rupture without orbital fracture.